Ethnomathematics Study: Arithmetic Sequence Patterns in the Rhythms of Traditional Musical Instruments of the Likurai Dance in Malaka Regency, East Nusa Tenggara - Kondradus Yohanes Klau; Oktovianus Mamoh (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2026)
This research is motivated by the importance of understanding the relationship between culture and mathematical concepts in community life. Ethnomathematics provides a field of study to reveal the existence of mathematical concepts embedded in the daily activities, traditions, and cultural practices of society. This study aims to identify and analyze arithmetic sequence patterns in the Bibiliku, a traditional musical instrument of the Likurai dance, which is essential to the community's Likurai dance in Malaka Regency, East Nusa Tenggara. This study employed a descriptive qualitative approach within the framework of ethnomathematics, using participatory observation, in-depth interviews with a traditional leader, a dancer, and a trainer, as well as audio-visual documentation. The findings reveal that the rhythmic patterns of Bibiliku in the “tabere” style form arithmetic sequences with a common difference of 2. Odd beats generate the sequence 1, 3, 5, 7, …, while even beats produce 2, 4, 6, 8, …. These results indicate that the rhythmic regularity of traditional music reflects mathematical concepts, particularly arithmetic sequences, although not formally defined by the community. The findings of this study can serve as contextual learning resources for teaching arithmetic sequences in mathematics education while also contributing to the preservation of cultural heritage.